1998
DOI: 10.1111/j.1399-3038.1998.tb00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study on latex sensitization in children with spina bifida

Abstract: The course of latex sensitization is rarely documented, and only a few reports about the influence of prophylaxis in the occupational environment have been published concerning health care workers. Therefore we did a follow-up study in the high risk group of patients with spina bifida and evaluated the efficacy of latex prophylaxis. For this purpose we measured IgE antibodies (FEIA) against latex and inhalative allergens in the sera of 67 patients with spina bifida and reevaluated them 0.6 to 4.1 years later, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 11 publications
2
15
0
2
Order By: Relevance
“…In the literature there is only one longitudinal investigation of latex sensitization in patients with spina bifida: in a 2 time point study with varying time intervals the authors concluded that surgery without strict latex prophylaxis is the main cause of new sensitization. 4 The same authors observed no new sensitization after having established latexfree surgery and anesthesia. 5 Our study considers three time points.…”
Section: Latex Allergy In Spina Bifida: At the Turning Point?mentioning
confidence: 90%
“…In the literature there is only one longitudinal investigation of latex sensitization in patients with spina bifida: in a 2 time point study with varying time intervals the authors concluded that surgery without strict latex prophylaxis is the main cause of new sensitization. 4 The same authors observed no new sensitization after having established latexfree surgery and anesthesia. 5 Our study considers three time points.…”
Section: Latex Allergy In Spina Bifida: At the Turning Point?mentioning
confidence: 90%
“…It is known that one case in a million inhabitants in the USA presents an anaphylactic shock caused by latex [6]. Health care staff, workers in the rubber industry, children with spina bifida, myelomeningocele or urogenital anomalies, food manipulators, hairdressers, and housewives are considered as a risk population [7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17]. In a study performed by us in health workers at the University Clinic of Navarra [18], we observed an incidence of latex allergy of 5%.…”
Section: Introductionmentioning
confidence: 99%
“…So konnten wir bei 21 Spina-bifida-Patienten 38 Operationen ohne allergische Reaktionen durchführen, wovon 4 Patienten eine symptomatische Latexallergie hatten, eine Patientin mit massiv erhöhten Latexantikörpern sogar mit einer intraoperativen Anaphylaxie [19]. So konnten wir bei 21 Spina-bifida-Patienten 38 Operationen ohne allergische Reaktionen durchführen, wovon 4 Patienten eine symptomatische Latexallergie hatten, eine Patientin mit massiv erhöhten Latexantikörpern sogar mit einer intraoperativen Anaphylaxie [19].…”
Section: Skin-prick-testunclassified